CLINICAL AND INSTRUMENTAL STUDY RESULTS OF COMPARING DIGITAL OCCLUSION INDICES AT REGISTRATION OF INTERCUSPAL POSITION IN PATIENTS WITH EDENTULOUS SPACES BEFORE AND AFTER PROSTHETIC REHABILITATION - Тaras Hlushko; Yuriy Vovk; Volodymyr Vovk; Petro Kryukov; Мaksym Lohash (Acta Medica Leopoliensia)
Aim. The research aims at carrying out a comparative clinical and instrumental analysis related to registering occlusal relations of intercuspal contact position in patients with edentulous spaces before and after prosthetic rehabilitation using various registration materials.